Design Rationality Territorial Branding Ancient Javanese Typography Visual Analysis Media Transcreation Kediri Square Script - Ipung Kurniawan Yunianto; Sunarmi Sunarmi (Brikolase : Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2026)
Studies on Old Javanese script have been dominated by an epigraphic approach that focuses on reading texts and historical dating, but often neglects its visual design aspects. This research fills this gap by deconstructing the Square Script (11th-13th century AD) through the perspective of Visual Communication Design (DKV) and Typography. Using a descriptive qualitative method with a visual archaeology approach, this research analyzes the morphology of the script in the PIM Mojokerto collection inscription, the technical data on the unfinished Tahi Papung inscription (Ponorogo), and its transfer to contemporary clothing media. The data are analyzed through tracing the morphology of the script, the application of modular grids and the Em Square principle, and visual semiotic interpretations to read the aesthetic and political functions of the script. The results of the study reveal three main findings. First, morphologically, the Square Script can be classified as a Slab Serif-style Display Typeface designed for long-distance visual dominance (visual weight). Second, the discovery of guidelines on the Tahi Papung artifact proves that this script was not written intuitively, but rather constructed through design rationality based on the Modular Grid system and the Em Square principle. Third, the combination of rigid geometric structures with dense ornamentation (Horror Vacui) functioned as a Territorial Branding strategy to legitimize the political power of the Kediri-Majapahit Kingdom. The transformation of this script into a creative industry product (a t-shirt) proves that this ancient design system possesses timeless qualities capable of adapting from its sacred-political function to a commodity of cultural identity.